2021
DOI: 10.1111/vcp.12994
|View full text |Cite
|
Sign up to set email alerts
|

Influence of preanalytical factors on feline proteinuria

Abstract: Background: To date, little information is available about the effect of preanalytical factors on the urinary protein-to-creatinine (UPC) ratio in cats.Objectives: We aimed to evaluate the effect of a commercially available cat litter, creatinine measurements at three different dilutions of urine, and different storage conditions on the UPC ratio in cats.Methods: Feline urine specimens were prospectively collected. Twenty-two wholeurine specimens were placed uncovered and in contact with cat litter for 1 hour;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 26 publications
(61 reference statements)
1
12
0
2
Order By: Relevance
“…Collection at home would have significant cost benefits to owners and might also reduce stress for feline patients. Our findings are in agreement with a recent study by Giraldi and others, which demonstrated that urine exposure to non‐absorbent plastic bead litter for 1 hour had no effect on feline UPC measurements 5 . However, our study evaluated the effect of a longer duration of exposure (24 hours) to better mimic what may happen in the home environment, where litter trays may only be emptied once a day.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Collection at home would have significant cost benefits to owners and might also reduce stress for feline patients. Our findings are in agreement with a recent study by Giraldi and others, which demonstrated that urine exposure to non‐absorbent plastic bead litter for 1 hour had no effect on feline UPC measurements 5 . However, our study evaluated the effect of a longer duration of exposure (24 hours) to better mimic what may happen in the home environment, where litter trays may only be emptied once a day.…”
Section: Discussionsupporting
confidence: 92%
“…Although urine samples were stored under different conditions, which may have affected UPC measurements, this study only compared the difference in UPC measurements taken 24 hours apart. Moyle and others showed that storage of urine at room temperature for up to 5 days did not affect UPC measurements in both proteinuric and non‐proteinuric dogs, and Giraldi and others showed that storage of urine at room temperature for 6 hours did not affect UPC measurements in cats 5,18 . In this study, all samples were brought to room temperature before baselineUPCs were measured.…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations